2015
DOI: 10.1002/2014jd022658
|View full text |Cite
|
Sign up to set email alerts
|

Dimming over the oceans: Transient anthropogenic aerosol plumes in the twentieth century

Abstract: Anthropogenic aerosols reduce incoming surface solar radiation (SSR), but the magnitude of this effect for reducing sea surface temperatures (SST) is still debated. Using simulations from the global climate model ECHAM5 with the Hamburg Aerosol Module and prescribed SSTs, we quantify anthropogenic aerosol dimming over sea surfaces by comparing ensembles, which only differ in anthropogenic aerosol emissions. We isolate the anthropogenic aerosol effect on SSR with sufficiently large ensemble sizes to provide sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
(106 reference statements)
1
10
0
Order By: Relevance
“…Thus, the MLO fraction of ocean area affected is lower for clear‐sky SSR and about five times as large for all‐sky SSR. Applying the same −4 W m −2 criterion to atmosphere only simulations of the 1990s, Dallafior et al [] found much more similar fractions, 9.4% for clear sky and 15.4% for all sky. This may point to significant, MLO‐related feedback processes.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, the MLO fraction of ocean area affected is lower for clear‐sky SSR and about five times as large for all‐sky SSR. Applying the same −4 W m −2 criterion to atmosphere only simulations of the 1990s, Dallafior et al [] found much more similar fractions, 9.4% for clear sky and 15.4% for all sky. This may point to significant, MLO‐related feedback processes.…”
Section: Resultssupporting
confidence: 91%
“…According to this analysis, most prominent oceanic regions susceptible to SSR changes caused by anthropogenic aerosols are located in the northern midlatitudes and extratropics, i.e., North Pacific, and the northern extratropical Pacific and Atlantic with sensitivities of tsurf toward all-sky SSR between 0.2 and 0.7 K W m −2 . For all-sky SSR, plume regions collocated with those identified by Dallafior et al [2015] show strong linear relationship with tsurf, namely, off the West African Coast, the Indian Ocean, and off East Asia. To a lesser extent, this also holds true for clear-sky SSR, where the plume regions with strong linearity are less extended than in all-sky SSR.…”
Section: Correlations Across Twentieth Century Equilibriamentioning
confidence: 94%
See 2 more Smart Citations
“…In addition to the studies focussing on the AMV, others found a longer-term impact of anthropogenic aerosols on downward surface solar radiation over the Atlantic and consequently SSTs (Dallafior et al, 2015), affecting the interhemispheric SST gradient and thereby causing a shift of the Atlantic Intertropical Convergence Zone (ITCZ; e.g., Chang et al, 2011;Hwang et al, 2013). Long-term anthropogenic aerosol forcing has furthermore been suggested to have strengthened the AMOC (Cowan & Cai, 2013;Delworth & Dixon, 2006;Menary et al, 2013) and to have delayed ocean heat content increase and associated sea level rise in response to greenhouse gas (GHG) forcing (e.g., Delworth et al, 2005) during the twentieth century.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%